2020
DOI: 10.1126/sciadv.abb2529
|View full text |Cite
|
Sign up to set email alerts
|

NuRD mediates mitochondrial stress–induced longevity via chromatin remodeling in response to acetyl-CoA level

Abstract: Mild mitochondrial stress experienced early in life can have beneficial effects on the life span of organisms through epigenetic regulations. Here, we report that acetyl–coenzyme A (CoA) represents a critical mitochondrial signal to regulate aging through the chromatin remodeling and histone deacetylase complex (NuRD) in Caenorhabditis elegans. Upon mitochondrial stress, the impaired tricarboxylic acid cycle results in a decreased level of citrate, which accounts for reduced production of acetyl-CoA and conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 44 publications
4
73
0
Order By: Relevance
“…An aging-induced decrease in nucleocytoplasmic acetyl-CoA levels could also contribute to the decreased histone H4K5 acetylation that occurs in aged worms. Consistent with this hypothesis, mitochondrial ETC dysfunction during larval development has been shown to decrease acetyl-CoA levels in C. elegans [ 386 ] and ETC dysfunction is a major phenotype of C. elegans aging [ 387 ]. Proteomics data has shown that the level of acetyl-CoA synthetase ACS-19, homologous to human ACSS2, decreases in post-reproductive worms and this decrease in ACS-19 abundance was delayed in long-lived daf-2 mutant worms [ 385 ].…”
Section: Nematode Changes In Histone Lysine Acetylation Marks With Aging and Anti-aging Dietary Restrictionmentioning
confidence: 88%
See 1 more Smart Citation
“…An aging-induced decrease in nucleocytoplasmic acetyl-CoA levels could also contribute to the decreased histone H4K5 acetylation that occurs in aged worms. Consistent with this hypothesis, mitochondrial ETC dysfunction during larval development has been shown to decrease acetyl-CoA levels in C. elegans [ 386 ] and ETC dysfunction is a major phenotype of C. elegans aging [ 387 ]. Proteomics data has shown that the level of acetyl-CoA synthetase ACS-19, homologous to human ACSS2, decreases in post-reproductive worms and this decrease in ACS-19 abundance was delayed in long-lived daf-2 mutant worms [ 385 ].…”
Section: Nematode Changes In Histone Lysine Acetylation Marks With Aging and Anti-aging Dietary Restrictionmentioning
confidence: 88%
“…Mitochondrial dysfunction during larval development was shown to result in decreased nucleocytoplasmic acetyl-CoA levels that decreased histone acetylation. The decreased level of acetyl-CoA was required for the proper activation of the UPR mt transcriptional response [ 386 ]. Adding back metabolites during the larval development that restored acetyl-CoA levels prevented induction of the UPR mt and lifespan extension.…”
Section: Decreased Acetyl-coa During C Elegans Development Is Required For the Upr Mt To Increase Lmentioning
confidence: 99%
“…It will be interesting to understand how these epigenetic marks coordinate with others to control mitochondrial homeostasis. In addition, two recent studies identified that histone deacetylase HDA-1, the catalytic component of nucleosome remodeling and deacetylase (NuRD) complex, is required for UPR mt activation 13,14 . It has been proposed that mitochondrial dysfunction may limit the availability of acetyl-CoA and that the NuRD complex or HDA-1 removes the acetyl moiety from histones, feeding additional acetyl-CoA into metabolic reactions.…”
Section: Ying Liumentioning
confidence: 99%
“…Dissection and fixation were carried out by freeze-crack method 84 . Worms were dissected in M9 buffer on a polylysine-coated slide.…”
Section: Intestinal Nuclei Analysismentioning
confidence: 99%
“…We used at least 30 worms in each sample for DAPI staining and intestinal nuclei from more than 10 worms were selected and quantified for nuclear size 84 .…”
Section: Intestinal Nuclei Analysismentioning
confidence: 99%